1995
DOI: 10.1037/0021-843x.104.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Backward masking performance during and after manic episodes.

Abstract: In a longitudinal design, 16 inpatients with bipolar mood disorder and 16 normal control participants were administered measures of backward masking. Bipolar inpatients were assessed while actively manic and again following manic episode. Clinical state was determined from ratings on an expanded version of the Brief Psychiatric Rating Scale. Two backward masking paradigms were used: (a) a staircase method, which yielded a critical interstimulus interval, and (b) set interstimulus intervals, which provided a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
3
24
1
Order By: Relevance
“…[3][4][5][6][7][8][9] Moreover, we observed that patients with BDI and BDII had abnormally low volume and/or thickness in medial occipital brain regions, including the cuneus, pericalcarine and lingual cortices. These findings are in line with previously reported deficits in visual processing and perception [36][37][38][39][40] -unrelated to lithium use 41,42 -and also with deficits in working memory tasks 10,[43][44][45][46] that partly engage visual areas of the medial occipital cortex. [47][48][49][50] Hence, it is not farfetched to assume that previously observed deficits in visual tasks in patients with BD might be partly related to neuroanatomical abnormalities in medial occipital brain regions.…”
Section: Cortical Abnormalities In Patients With Bdi and Bdiisupporting
confidence: 82%
“…[3][4][5][6][7][8][9] Moreover, we observed that patients with BDI and BDII had abnormally low volume and/or thickness in medial occipital brain regions, including the cuneus, pericalcarine and lingual cortices. These findings are in line with previously reported deficits in visual processing and perception [36][37][38][39][40] -unrelated to lithium use 41,42 -and also with deficits in working memory tasks 10,[43][44][45][46] that partly engage visual areas of the medial occipital cortex. [47][48][49][50] Hence, it is not farfetched to assume that previously observed deficits in visual tasks in patients with BD might be partly related to neuroanatomical abnormalities in medial occipital brain regions.…”
Section: Cortical Abnormalities In Patients With Bdi and Bdiisupporting
confidence: 82%
“…During VBM a stimulus is presented for a very short fixed period of time before being replaced by a non-informative mask. BD patients appear to have impaired performance both during and after a manic episode (Fleming & Green, 1995). MacQueen et al (2001) found that medicated euthymic BD subjects were impaired at both identifying what the stimulus was and where on the display screen it had been located.…”
mentioning
confidence: 99%
“…However, it is unclear if impaired backward masking is specific to schizophrenia spectrum disorders (Rund et al, 2004). Studies comparing backward masking performance of subjects with bipolar disorder to that of non-patients have been inconsistent (Saccuzzo and Braff, 1981;Green andWalker, 1986;Rund, 1993;Green et al, 1994a;Fleming and Green, 1995;MacQueen et al, 2001). Studies comparing backward masking performance of subjects with major depression without psychotic features to that of nonpatients, on the other hand, consistently find no differences Braff, 1981, 1986;Elkins et al, 1992;Arolt, 1997, 1998;Rund et al, 2004).…”
Section: Introductionmentioning
confidence: 99%